Neuroendocrine and reproductive aspects of adult male rats exposed neonatally to an antiestrogen - Gerardin, DCC; Bemardi, M. M.; Moreira, E. G.; Pereira, OCM (Elsevier B.V., 2006)
The present study was designed to investigate the effects of a single dose of an estrogen antagonist-clomiphene-during neonatal life, on later neuroendocrine system and reproductive performance. Immediately after birth, male pups received clomiphene citrate (s.c.). At adulthood, although testosterone levels and wet weights of reproductive organs were not altered, the treatment induced an increased number of spermatozoa and a delay in the transit time in the cauda epididymis. Additionally, there was impairment of sexual behavior evidenced by a delay in the latencies to the first mount and first intromission. Treated rats also showed decreased dopaminergic and serotonergic neurotransmissions in the hypothalamus and decreased dopaminergic neurotransmission in the striatum. The decreased dopaminergic activity could be related to the lower sexual motivation observed. These results indicate the necessity of preventing exposure to drugs that may impair sexual differentiation, which can compromise later mating success as well as the capacity to generate descendants. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: antiestrogen; clomiphene; hypothalamus; neurochemistry; rat; sexual behavior; sexual differentiation; spermatozoa; striatum; testosterone